CARS based label‐free assay for assessment of drugs by monitoring lipid droplets in tumour cells. Issue 11 (17th December 2013) - Steuwe, Christian; Patel, Imran I.; Ul‐Hasan, Mahmud; Schreiner, Alexander; Boren, Joan; Brindle, Kevin M.; Reichelt, Stefanie; Mahajan, Sumeet
Abstract Coherent anti‐Stokes Raman scattering (CARS) is becoming an established tool for label‐free multi‐photon imaging based on molecule specific vibrations in the sample. The technique has proven to be particularly useful for imaging lipids, which are abundant in cells and tissues, including cytoplasmic lipid droplets (LD), which are recognized as dynamic organelles involved in many cellular functions. The increase in the number of lipid droplets in cells undergoing cell proliferation is a common feature in many neoplastic processes [1] and an increase in LD number also appears to be an early marker of drug‐induced cell stress and subsequent apoptosis [3]. In this paper, a CARS‐based label‐free method is presented to monitor the increase in LD content in HCT116 colon tumour cells treated with the chemotherapeutic drugs Etoposide, Camptothecin and the protein kinase inhibitor Staurosporine. Using CARS, LDs can easily be distinguished from other cell components without the application of fluorescent dyes and provides a label‐free non‐invasive drug screening assay that could be used not only with cells and tissues ex vivo but potentially also in vivo. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)